ANATOL EREMIA – A “GUARDIAN” OF TOPONYMY - Aurelia HANGANU (Academy of Sciences of Moldova, 2021)
This year, 2021, on July 3, the researcher Anatol Eremia turns 90 years old. He is the personality who remained faithful during his entire scientific career to the Institute of Romanian Philology “Bogdan Petriceicu-Hasdeu“, in its various forms of existence so far. He dedicated his life to onomastics research, demonstrating a special predilection for the phenomena of toponymy. Evolving in his career at all levels of the academic hierarchy, from laboratory in the field of Onomastics to scientific coordinator and scientific consultant, he managed to gather scientific information and make relevant analyzes by publishing 25 monographs, dictionaries, guides and 465 scientific articles and popularization of science. Among the most famous works signed by Anatol Eremia are: Names of localities. Toponymy study, 1970; The secrets of geographical names, 1986; The unity of the Romanian onomastic patrimony, 2001; Cahul in time and space, 2007; Chisinau. History and current affairs, 2012; The Romanian toponymic treasure. Republic of Moldova. Cantemir area, 2016; Leova. Localities, people, traditions, 2018 etc. His contribution is not limited to actual research or training of qualified staff in the field. He has had and continues to work in several commissions, councils, editorial boards dealing with issues of onomastics (toponymy, anthroponymy): UN Expert Group for Standardization of Geographical Names of International Circulation, Scientific Council of the Institute of Romanian Philology, Interdepartmental Commission for Study the state and development of the Romanian language, the Republican Commission for the regulation and protection of national onomastics, the Commission for the regulation of urbanism of Chisinau, the Editorial Board of the dedicated journal. Anatol Eremia is a patrimonial personality for onomastic and toponymic research, who became, in time, a “guardian” of toponymy, as he had once been a “guardian” in the Romanian school of Cahul.